THE RE-PROCESSING RESULTS OF PHOTOGRAPHIC OBSERVATIONS OF ASTEROIDS WITH GAIA CATALOG AT THE MAO NAS OF UKRAINE - Shatokhina, S V.; Kazantseva, L. V.; Andruk, V. M. (Одеські астрономічні публікації, 2019)
In total, about 4,500 asteroid po-sitions were determined from photographic observations conducted at the MAO NAS of Ukraine in 1952-1996. These are the early positions of the selected minor planets, mostly bright, the observations of which were initiated by the founders of the ORBITA observational program and were made in 1952-1986. The second later positions of asteroids obtained from digitized plates from photographic observations of the Northern Sky Survey project in 1981-1996. Using digital plate processing technologies, 2292 asteroid positions were obtained, the images of which were fixed during observations and identified during processing.The new star catalog Gaia DR2 was used to study changes in determining the accuracy of equatorial coordinates for various faint objects on plates. For several 8 plates with images of Pluto comets and faint asteroids of particular interest due to the lack of observations in the past, new complete processing of scans of these plates was performed. The Gaia DR2 was used as a reference catalog. The asteroid positions from early observations of 1952- 1986 were determined in accordance with classical linear reduction algorithms. These are 1651 positions of minor planets determined in the PPM catalog system and obtained from observations with the Double Wide-Angle Astrograph. The remaining 591 positions were determined in the systems of old reference catalogs of stars Yale, SAO, AGK3, and obtained from observations with the Double Long-Focus Astrograph. It was for these positions that the calibration with the Gaia catalog was performed. The data on the positions of minor planets digitized from publications and additional data on their reference systems deposited in previous years at VINITI (now VINITI Database RAS) were used. Comparison with JPL ephemeris was performed both for new determinations of asteroid coordinates with the Gaia catalog, and for past determinations obtained in systems of other reference catalogs.